1994
DOI: 10.3109/10428199409049704
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Results of Interferon Treatment in Hairy Cell Leukemia Italian Cooperative Group of Hairy Cell Leukemia (ICGHCL)

Abstract: Eighty nine of 104 patients with hairy cell leukemia (HCL), enrolled between 1985 and 1987 in a multicenter prospective study on human lymphoblastoid IFN alpha-n1, were evaluable for long-term follow-up. The induction treatment, 3 MU/mq daily for a median of 5.7 months, produced a response of 93%, complete+partial response (CR+PR) = 80%, minor (MR) = 13%. Neither prior splenectomy nor pre-treatment variables were associated with the rate of response to IFN. However maintenance treatment of 3 MU/mq weekly given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This finding has been corroborated by other investigators. A large, multicenter, prospective trial of 104 HCL patients lead by the Italian Cooperative Group of Hairy Cell Leukemia (ICGHCL) showed an overall response rate of 93%, with a CR rate of 13% [50]. Several mechanisms have been postulated for the rapid activity of interferon in HCL.…”
Section: Treatmentmentioning
confidence: 99%
“…This finding has been corroborated by other investigators. A large, multicenter, prospective trial of 104 HCL patients lead by the Italian Cooperative Group of Hairy Cell Leukemia (ICGHCL) showed an overall response rate of 93%, with a CR rate of 13% [50]. Several mechanisms have been postulated for the rapid activity of interferon in HCL.…”
Section: Treatmentmentioning
confidence: 99%
“…Quesada et al (13) first described the efficacy of IFN in HCL and subsequently other studies clearly demonstrated that IFN is an effective treatment for HCL, both as initial therapy and in previously treated patients (2, 14–16). Moreover, IFN‐ α therapy resulted in recovery of immunological function in patients with HCL characterized by an increase in the number of monocytes and a restoration of natural killer and T cell function (17, 18).…”
Section: Discussionmentioning
confidence: 99%